2022
DOI: 10.1186/s42238-022-00143-y
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis-only use in the USA: prevalence, demographics, use patterns, and health indicators

Abstract: Background The prevalence of adults who consume cannabis while abstaining from other substances is not known in the USA. This study used nationally representative data to estimate the prevalence and explore the demographic characteristics, cannabis use behaviors, and self-reported health of US adults with past 30-day cannabis-only use, as compared with adults who used cannabis as well as other substances. Methods Data came from adults 18 years and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…Finally, current findings indicate that certain groups of parents may require focused attention, such as cannabis and alcohol users.LimitationsFirst, this study has limited generalizability to other parent populations, as the sample was drawn from six MSAs in the United States, largely White and female, and recruited via social media into a study regarding tobacco use. One-third (33.5%) of participants reported past-month cannabis use, which is higher than other national estimates of 12.2% among adults ages 26-4934 and likely due to our recruitment strategy (representation of tobacco users and MSAs with recreational cannabis). Second, data were self-reported, which has potential for biased reporting.…”
contrasting
confidence: 60%
“…Finally, current findings indicate that certain groups of parents may require focused attention, such as cannabis and alcohol users.LimitationsFirst, this study has limited generalizability to other parent populations, as the sample was drawn from six MSAs in the United States, largely White and female, and recruited via social media into a study regarding tobacco use. One-third (33.5%) of participants reported past-month cannabis use, which is higher than other national estimates of 12.2% among adults ages 26-4934 and likely due to our recruitment strategy (representation of tobacco users and MSAs with recreational cannabis). Second, data were self-reported, which has potential for biased reporting.…”
contrasting
confidence: 60%
“…With the gradual legalization and social acceptance of cannabis in the United States, its risk for abuse has increased significantly ( Hasin et al, 2015 ; Carliner et al, 2017 ). A recent study by Carlini and Schauer (2022) reported the age-related prevalence of cannabis use among US adults. Adolescent to young adults, 18–25 years old, have the highest prevalence (2.0%) of cannabis use-only followed by 26–49 years old (0.7%), and 0.6% for over 50 years of age ( Carlini and Schauer, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Carlini and Schauer (2022) reported the age-related prevalence of cannabis use among US adults. Adolescent to young adults, 18–25 years old, have the highest prevalence (2.0%) of cannabis use-only followed by 26–49 years old (0.7%), and 0.6% for over 50 years of age ( Carlini and Schauer, 2022 ). Whereas 9.4% of the general population use cannabis with other drugs like nicotine and alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…The use of cannabis products containing high concentrations of THC is rapidly increasing; yet we still have a limited understanding of its possible impact on physical and mental health (13). These products are typically inhaled as combusted plant matter, vaporized extracts or increasingly ingested in edible forms.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Cannabis products containing high concentrations of THC is rapidly increasing despite our limited understanding of its potential impact on physical and mental health [1][2][3].…”
Section: Introductionmentioning
confidence: 99%